Photovoltaic nano antibacterial material MXene (at) MOF and preparation method thereof

By uniformly coating the porphyrin-based 2D metal organic framework (MOF) on the MXene surface, photocatalytic and photothermal pathways are used to coordinate antibacterial antibacterial, the problem of poor effectiveness and high cost of existing nanoantibacterial materials against drug-resistant bacteria is solved. It achieves efficient removal of MRSA and improves material performance.

CN119158603APending Publication Date: 2024-12-20SHANGHAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411299678.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing nanoantibacterial materials are prone to bacterial resistance when fighting drug-resistant bacteria such as MRSA, and are costly to produce, which limits their popularization of applications.

Method used

Develop a photovoltaic nano-anti-bacterial material, MXene@MOF, by uniformly coating the porphyrin-based 2D metal organic framework (MOF) on the surface of MXene, using photocatalysis and photothermal dual pathways to jointly antibacterial, improve the oxygen radical generation rate and antibacterial efficiency. Make up for the inherent defects of a single material.

Benefits of technology

It has achieved efficient removal of drug-resistant bacteria, improved the photothermal conversion efficiency and antibacterial performance of the material, reduced the minimum inhibitory concentration, and had good biomedical application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158603A_ABST
    Figure CN119158603A_ABST
Patent Text Reader

Abstract

The invention discloses a photovoltaic nano antibacterial material MXene (at) MOF and a preparation method thereof. The MXene (at) MOF is composed of an MXene substrate and a 2D metal organic framework (MOF) layer, wherein the MXene substrate is composed of two-dimensional transition metal carbide, nitride or carbonitride, and the surface of the MXene substrate is evenly coated with the 2D metal organic framework (MOF) layer. The material combines high conductivity, hydrophilicity and adjustable chemical composition of MXene with excellent photovoltaic response characteristic, adjustable chemical structure and stability of MOF, and realizes a photocatalytic and photo-thermal dual-channel synergistic antibacterial strategy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to antibacterial materials, and in particular to a photovoltaic nano antibacterial material MXene@MOF and a preparation method thereof. Background Art

[0002] Methicillin-resistant Staphylococcus aureus (MRSA) is a strain that is resistant to multiple types of antibiotics. It can cause infections in the skin, soft tissue, respiratory tract, blood and other parts of the body. In severe cases, it can even lead to sepsis, pneumonia, etc. MRSA's resistance to antibiotics is more than three orders of magnitude higher than that of ordinary bacteria. Therefore, technicians in this field urgently need to seek simple, safe, and efficient antibiotic-free treatment strategies to effectively combat MRSA. Traditional nano-antibacterial materials usually exert their antibacterial effects through mechanisms such as releasing ions or directly destroying bacterial cell walls. This single antibacterial mechanism easily leads to bacterial resistance. The preparation cost of nano-antibacterial materials is relatively high, which also limits their popularity and promotion in practical applications. Summary of the invention

[0003] MXene is a material composed of two-dimensional transition metal carbides, nitrides or carbonitrides, which have a layered structure similar to graphene. The name of MXene materials comes from their constituent elements, where "M" represents transition metal elements such as titanium (Ti), zirconium (Zr), niobium (Nb), etc., and "X" represents carbon (C), nitrogen (N) or carbon nitrogen (CN). MXene materials have the following characteristics: High conductivity: Due to the presence of transition metals in their structure, MXene materials generally have high electrical conductivity. Hydrophilicity: MXene surfaces usually have functional groups such as hydroxyl or fluorine groups, which make them well dispersed and hydrophilic in water. Adjustable chemical composition: By changing the elements and conditions during the synthesis process, the chemical composition of MXene can be adjusted, thereby affecting its performance. Excellent mechanical properties: MXene materials generally have high strength and flexibility. Versatility: MXene can be compounded with other materials to form composite materials with specific functions. Environmental stability: Compared with graphene, MXene may show better stability in certain environments. The biocompatibility and hydrophilicity of MXene make it promising for application in the biomedical field.

[0004] Porphyrin-based 2D metal-organic frameworks (MOFs) have excellent photovoltaic response characteristics, tunable chemical structures, and outstanding stability. When the 2D MOF layer is uniformly coated on the MXene surface, it can be used to control the molecular penetration of the composite structure surface due to its small and uniform pore size. 2D MOF enhances the oxidative stability of MXene. More importantly, the porphyrin-based 2D MOF with photocatalytic properties introduces a second efficient light-driven antibacterial strategy for heterojunctions. From another perspective, in view of the poor electrical properties of MOF and the limitations of easy recombination of electrons / holes, MXene provides excellent light absorption and effective electron transfer channels for 2D heterojunctions, which helps to separate the photogenerated electrons / holes of 2DMOF to improve the yield of oxygen free radicals (ROS). MXene enhances the photovoltaic performance of 2D MOF. MXene@MOF not only integrates a dual-pathway (photocatalytic and photothermal) synergistic antibacterial strategy, but also makes up for the inherent defects of a single material.

[0005] One of the purposes of the present invention is to develop a new photovoltaic nano antibacterial material MXene@MOF to achieve the removal of drug-resistant bacteria.

[0006] The second object of the present invention is to provide a method for preparing the antibacterial material.

[0007] To achieve the above object, the present invention of the method adopts the following mechanism:

[0008] MAX parent phase is stripped into Ti3C2T x MXene nanosheets; organic ligand tetrakis(4-carboxyphenyl)porphine (TCPP) is connected to the MXene surface through the coordination of carboxyl and metal Ti; precursor substances and surfactants are added to the system, and MXene@MOF is successfully synthesized by solvothermal method. MXene@MOF with stable and enhanced photovoltaic performance shows excellent photothermal and photocatalytic ability under light, which provides a guarantee for efficient MRSA removal.

[0009] MXene@MOF not only integrates photocatalytic and photothermal functions to achieve dual-channel synergistic antibacterial, but also solves the inherent defects of a single material to enhance the overall photovoltaic performance. On the one hand, the outer layer of MOF makes up for the defect of MXene's easy oxidation to improve the photothermal conversion efficiency and photothermal stability of MXene. On the other hand, in response to the limitations of MOF's photovoltaic performance, MXene provides excellent light absorption and effective electron transfer channels to improve the photocatalytic efficiency. The interface delocalization effect promotes the enrichment of MOF's photogenerated carriers on the MXene surface, and the Schottky barrier prevents the photogenerated carriers from migrating back. The symbiosis-inspired bidirectional interaction design not only improves the photogenerated electron / hole separation efficiency of MOF, but also improves the utilization rate of MXene for hot electrons, providing a guarantee for efficient dual-channel synergistic antibacterial.

[0010] In summary, the protection of MOF improves the photothermal performance of MXene, and MXene improves the photocatalytic effect of MOF, achieving a dual-pathway synergistic antibacterial effect.

[0011] Specifically, the present invention first provides a method for preparing a photovoltaic nano antibacterial material MXene@MOF, comprising the steps of:

[0012] (1) Synthesis of MXene: HCl and LiF are added to a reactor to react and generate an etching solution; Ti3AlC2 is slowly added to the etching solution in small amounts to perform an etching reaction; after the reaction is completed, the mixture is repeatedly centrifuged and washed to remove the acid solution until the pH of the supernatant is close to neutral; then the Ti3C2T x Become a single-layer MXene;

[0013] (2) Synthesis of MOF: Cu(NO3)2, trifluoroacetic acid, PVP and TCPP were subjected to hydrothermal reaction in a mixed solution of DMF and ethanol. After the reaction, the solution was cooled to room temperature, centrifuged and washed with ethanol to obtain a two-dimensional MOF solution.

[0014] (3) Synthesis of MXene@MOF: MXene was dissolved in DMF and ethanol, TCPP was added and mixed evenly, and then allowed to stand at room temperature to obtain solution A. Cu(NO3)2, trifluoroacetic acid, and PVP were dissolved in DMF and ethanol to obtain solution B. Solution A was slowly added to solution B and ultrasonically mixed. The mixed solution was deoxygenated with nitrogen and then placed in a reactor for reaction. The obtained solution was centrifuged and washed with DMF and then redissolved in DMF to obtain MXene@MOF.

[0015] Furthermore, in the synthesis step of MXene, 40 mL of 9 M HCl and 3.2 g of LiF were added to a polytetrafluoroethylene reactor and reacted for 20 minutes to prepare an etching solution; 2 g of Ti3AlC2 was slowly added to the etching solution in small amounts at a rotation speed of 500 rpm, and reacted at 40°C for 48 hours.

[0016] Further, in the MOF synthesis step, 3.6 mg, 0.015 mmol Cu(NO3)2, 10 μL 1.0 M trifluoroacetic acid, 10.0 mg PVP and 4.0 mg, 0.005 mmol TCPP were hydrothermally synthesized in 16 mL, V:V = 3:1 mixed solution of DMF and ethanol at 80 °C for 3 h.

[0017] Furthermore, in the synthesis step of MXene@MOF, 1 mg MXene was dissolved in 16 mL, V:V=3:1 DMF and ethanol, and 4 mg TCPP was added as solution A; 3.6 mg, 0.015 mmol Cu(NO3)2, 10 μL 1.0 M trifluoroacetic acid, and 10.0 mg PVP were dissolved in 48 mL, V:V=3:1 DMF and ethanol as solution B; solution A was slowly added to solution B, and the mixture was reacted at 85°C in a reactor for 3 h.

[0018] The present invention also provides a photovoltaic nano-antibacterial material MXene@MOF, which is prepared by the above-mentioned preparation method and has a MXene substrate and a MOF layer. The MOF layer is uniformly coated on the surface of the MXene substrate, which enhances the oxidative stability of MXene and integrates photocatalytic and photothermal functions to achieve dual-pathway synergistic antibacterial.

[0019] The present invention also provides an antibacterial method using the MXene@MOF material as described above, which stimulates the photothermal and photocatalytic capabilities of the MXene@MOF material through light to eliminate drug-resistant bacteria.

[0020] Furthermore, the MXene@MOF material was irradiated with 808 nm near-infrared light.

[0021] The present invention designs a composite nanomaterial based on MXene, which can enhance the photothermal and antibacterial properties of MXene. The experimental results show that the method has a high photothermal conversion coefficient and a high bactericidal efficiency. The test results show that the method has a lower minimum inhibitory concentration (MIC). MOF enhances the oxidative stability of MXene, thereby improving its photothermal conversion efficiency and antibacterial properties. MXene provides excellent light absorption and effective electron transfer channels for 2D heterojunctions, and improves the yield of oxygen free radicals (ROS) by helping to separate the photogenerated electrons / holes of 2DMOF, thereby improving its photocatalytic effect.

[0022] The concept, specific structure and technical effects of the present invention will be further described below in conjunction with the accompanying drawings to fully understand the purpose, characteristics and effects of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a characterization diagram of the synthetic material in a preferred embodiment of the present invention, wherein (A) is a TEM image of MXene; (B) is a TEM image of MOF; (C) is a TEM image of MXene@MOF; (D) is a UV-Vis spectrum of MXene, MOF, TCPP, and MXene@MOF; (E) is a FTIR spectrum of MXene, MOF, TCPP, and MXene@MOF.

[0024] Figure 2 This is a verification of the photothermal performance of the synthesized material in a preferred embodiment of the present invention, wherein (A) is a thermal imaging image of MOF, MXene, and MXene@MOF under 808nm near-infrared light irradiation for ten minutes; (B) is a heating curve of MXene@MOF with different concentrations; and (C) is a three-temperature heating and cooling cycle diagram of MXene@MOF.

[0025] Figure 3 This is a verification of catalytic performance in a preferred embodiment of the present invention, wherein (A) is the UV-vis spectrum image of TMB in different reaction systems; (B) is the determination of the steady-state kinetics of TMB at different concentrations by M@M. (C) is the fitted Michaelis-Menten equation curve of TMB concentration change and reaction rate.

[0026] Figure 4 This is a verification of the antibacterial performance in a preferred embodiment of the present invention, wherein (A) is the survival rate of E. coli after being treated with 808nm near-infrared light for 10 minutes at different concentrations of MXene@MOF; (B) is the survival rate of S. aureus after being treated with 808nm near-infrared light for 10 minutes at different concentrations of MXene@MOF; (C) is the survival rate of MRSA after being treated with 808nm near-infrared light for 10 minutes at different concentrations of MXene@MOF. DETAILED DESCRIPTION

[0027] The following describes several preferred embodiments of the present invention with reference to the drawings in the specification, so that the technical content is clearer and easier to understand. The present invention can be embodied in many different forms of embodiments, and the protection scope of the present invention is not limited to the embodiments mentioned in the text.

[0028] The preparation, photothermal performance verification, photocatalytic performance verification and antibacterial methods and steps of MXene@MOF in this embodiment are as follows:

[0029] (1) Synthesis steps of MXene@MOF:

[0030] Synthesis of MXene: Add 40mL 9M HCl and 3.2g LiF to a polytetrafluoroethylene reactor and react for 20 minutes to prepare an etching solution. Slowly add 2g of Ti3AlC2 to the etching solution in small amounts at 500rpm and react at 40℃ for 48h. After the reaction, centrifuge and wash repeatedly at 5000rpm for 5min to remove the acid until the pH of the supernatant is close to neutral. Then shake vigorously to turn Ti3C2Tx into a single layer of MXene. Finally, centrifuge the solution at 3500rpm for more than 30 minutes, and collect the supernatant containing the layered flakes for further use.

[0031] Synthesis of MOF: Cu(NO3)2 (3.6 mg, 0.015 mmol), trifluoroacetic acid (1.0 M × 10 μL), PVP (10.0 mg) and TCPP (4.0 mg, 0.005 mmol) can be hydrothermally synthesized at 80 ° C for 3 hours in a mixed solution of DMF and ethanol (16 mL, V: V = 3: 1). After stopping heating, the solution was cooled to room temperature, centrifuged at 8000 r.pm for 10 minutes, and washed twice with ethanol to obtain a red-purple two-dimensional MOF solution. Finally, the obtained two-dimensional MOF was redissolved in 10 mL of ethanol solution and stored at 4 ° C.

[0032] Synthesis of MXene@MOF: 1 mg MXene was dissolved in DMF and ethanol (16 mL, V:V = 3:1), 4 mg TCPP was added, ultrasonicated for 30 min and stirred for 2 h to mix evenly, and then allowed to stand at room temperature for 2 h, as solution A. Cu(NO3)2 (3.6 mg, 0.015 mmol), trifluoroacetic acid (1.0 M × 10 μL), and PVP (10.0 mg) were dissolved in DMF and ethanol (48 mL, V:V = 3:1) as solution B. Solution A was slowly added to solution B and ultrasonically mixed for 10 min. The solution was deoxygenated with nitrogen to ensure that there was no oxygen in the mixed solution. It was placed in a reactor and reacted at 85 ° C for 3 h. The obtained solution was centrifuged and washed three times with DMF at 12000 r / min. Finally, it was redissolved in 10 mL DMF. The above three materials were characterized by TEM, SEM, XPS, FTIR, UV-Vis, and Zeta.

[0033] (2) Characterization of MXene@MOF and verification of photothermal and photocatalytic properties:

[0034] Transmission electron microscope (TEM) images were taken using a JEM-2100F microscope (Japan). UPS spectra were recorded using a ThermoFisher K-Alpha (USA - Thermo Fisher). Fourier transform infrared spectra (FTIR) were recorded using a VERTEX 70 (Bruker, Germany). Ultraviolet-visible (UV-Vis) spectra were recorded using a Shimadzu UV-2450PC UV-visible spectrophotometer (Shimadzu, Japan). Infrared thermal imaging images and temperature values ​​were recorded using a photothermal camera (Fortric 225s). 808nm 1W / cm 2 The laser was obtained by 808MLKH1000-GY (Dongwan Yizheng Electronic Technology Co., Ltd.).

[0035] To verify the photothermal performance of M@M, 1, 10, 100 μg / mL and 1 mg / mL of M@M were irradiated with 808 nm laser for 10 min, the laser power was 1 w / cm2, and the temperature reading was recorded every 60 seconds for 10 min. The photothermal stability was determined by three cycles of switching on and off, each cycle lasting 20 minutes.

[0036] The photocatalytic activity was verified by TMB. 25uL H2O2 (2.5, 5, 7.25, 10, 12.5mM), 25μLTMB (1, 2, 3, 4, 6, 8, 10, 12, 15mM) and 50μL M@M (1, 5, 10, 100μg / mL) were co-incubated and irradiated under near-infrared light at 808nm for 10min. The absorption peak of TMB at 652nm was measured by UV spectrophotometer.

[0037] (3) Verification of antibacterial properties of MXene@MOF:

[0038] 10 μg / mL of MXene@MOF, MXene and MOF were used to verify its antibacterial performance against MRSA. Escherichia coli (E. coli), Staphylococcus aureus (S. aureus) and methicillin-resistant Staphylococcus aureus (MRSA) were used as bacterial models to evaluate the ability of MXene@LM to release intramembrane proteins from bacteria.

[0039] Escherichia coli, Staphylococcus aureus and MRSA were inoculated into agarose medium in three streaks and cultured at 37°C for 24 hours. A single colony of the cultured bacteria was inoculated into 100 mL of LB medium, placed in a shaker, and cultured at 37°C and 130 rpm for 18 hours. The resulting bacterial solution was diluted to 2*10 with PBS. 4 CFU / mL was used for subsequent experiments. Three bacteria, appropriate concentrations of materials, PBS and H2O2 (2.5mM) were co-incubated. Each group of samples was irradiated with NIR as the experimental group, and the control group was not irradiated. After irradiation, 100μL of 1mL sample was plated into agarose medium and cultured at 37℃ for 24h. The next day, photos were taken and the results were analyzed.

[0040] See attached figure, Figure 1 Characterization diagrams of the synthesized materials. (A) is the TEM image of MXene. (B) is the TEM image of MOF. (C) is the TEM image of MXene@MOF. (D) is the UV-Vis spectra of MXene, MOF, TCPP, and MXene@MOF. (E) is the FTIR spectra of MXene, MOF, TCPP, and MXene@MOF.

[0041] As can be seen from the figure: Figure 1 A shows MXene ultrathin nanosheets. Figure 1 B TEM shows that it has an ultra-thin and flat 2DMOF sheet structure. Figure 1 D shows that the peak of TCPP at 1525 cm-1 corresponds to the stretching vibration of the carboxyl C=O group. Figure 1 C shows that many 2D MOFs are folded and grown on larger MXene sheets, indicating that MXene@MOF is a multi-layer folded 2D heterojunction. After MXene is coordinated with TCPP, double peaks of MXene@TCPP appear at 1718cm-1 and 1466cm-1, corresponding to the stretching vibration of CO-O-Ti. Figure 1 As shown in E, compared with TCPP, the four weak absorption peaks of the q band of MXene@MOF are converted into one strong absorption peak, and the characteristic peak of the porphyrin ring is slightly red-shifted. This indicates that the carboxyl group of MXene@TCPP has been bound to Cu 2+ The ions were successfully coordinated, and the porphyrin ring center of TCPP was successfully metallated. The above results indicate the successful preparation of MXene@MOF.

[0042] See attached figure, Figure 2 The photothermal performance of the synthesized materials is verified as follows: (A) Thermal imaging of MOF, MXene, and MXene@MOF under 808nm near-infrared light irradiation for ten minutes. (B) Heating curves of MXene@MOF with different concentrations. (C) Three heating and cooling cycles of MXene@MOF.

[0043] As can be seen from the figure, the photothermal capacity of MXene@MOF is significantly enhanced compared with MXene and MOF, and remains stable after multiple temperature increases.

[0044] See attached figure, Figure 3 To verify the catalytic performance, specifically: (A) UV-vis spectra of TMB in different reaction systems. (B) M@M determination of the steady-state kinetics of TMB at different concentrations. (C) Fitting of the Michaelis-Menten equation curve of TMB concentration change and reaction rate.

[0045] As can be seen from the figure, Figure 3 A shows that MXene alone does not have photocatalytic properties. Compared with the dark environment, NIR irradiation can significantly enhance the catalytic performance of MOF. MOF catalyzes and decomposes H2O2 to produce a large number of hydroxyl radicals (·OH) to oxidize TMB, thereby showing the characteristic peak of oxTMB at 652nm. MXene@MOF prepared by heterojunction engineering has only weak catalytic performance under dark conditions. It is worth noting that the ability of M@M to catalyze H2O2 is significantly improved after NIR irradiation. Figure 3B shows that within the TMB gradient concentration range, the time to enter the plateau phase continues to decrease, indicating that the rate of the photocatalytic reaction increases with the increase of TMB concentration. According to the Michaelis-Menten equation, the K m and the maximum reaction rate (V max ) are calculated as K m =9.64mM,V max =0.81μM / s.

[0046] See attached figure, Figure 4 To verify the antibacterial properties, specifically: Figure 4 (A) The survival rate of E. coli after 10 minutes of treatment with 808nm near-infrared light at different concentrations of MXene@MOF. (B) The survival rate of S. aureus after 10 minutes of treatment with 808nm near-infrared light at different concentrations of MXene@MOF. (C) The survival rate of MRSA after 10 minutes of treatment with 808nm near-infrared light at different concentrations of MXene@MOF.

[0047] As can be seen from the figure, compared with MXene and MOF, MXene@MOF has a stronger antibacterial effect on E.coli, S.aureus and MRSA under 808nm near-infrared light excitation. The minimum inhibitory concentration is 10μg / mL. The above results show that MXene@MOF has excellent antibacterial properties.

[0048] The present invention utilizes the interaction between MOF and MXene to enhance the photothermal and antibacterial properties of MXene. The material has high antibacterial properties against MRSA and can kill more than 99% of bacteria after 10 minutes of illumination at a concentration of 10 μg / mL. The material has good application prospects in the biomedical field, especially in the prevention and treatment of drug-resistant bacteria.

[0049] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A method for preparing photovoltaic nano-antibacterial material MXene@MOF, It is characterized in that Includes steps: (1) Synthesis of MXene: HCl and LiF are added to the reactor to generate etching solution; Ti 3 AlC 2 Slowly add etching solution in small amounts to carry out etching reaction. After the reaction is completed, centrifuge and wash repeatedly to remove the acid solution until the pH of the supernatant is close to neutral; then shake the Ti 3 C 2 T x Become a single-layer MXene; (2) Synthesis of MOF: Cu(NO 3 ) 2 , trifluoroacetic acid, PVP and TCPP are subjected to hydrothermal reaction in a mixed solution of DMF and ethanol; after the reaction, the solution is cooled to room temperature, centrifuged and washed with ethanol to obtain a two-dimensional MOF solution; (3) Synthesis of MXene@MOF: MXene was dissolved in DMF and ethanol, TCPP was added and mixed evenly, and then allowed to stand at room temperature to form solution A. Cu(NO 3 ) 2 , trifluoroacetic acid, and PVP were dissolved in DMF and ethanol as solution B; solution A was slowly added to solution B and ultrasonically mixed; the mixed solution was deoxygenated with nitrogen and placed in a reactor for reaction. The obtained solution was centrifuged and washed with DMF and then redissolved in DMF to obtain MXene@MOF.

2. The method for preparing the photovoltaic nano antibacterial material MXene@MOF according to claim 1, in, In the synthesis step of MXene, 40 mL of 9 M HCl and 3.2 g of LiF were added to a polytetrafluoroethylene reactor and reacted for 20 minutes to prepare an etching solution; 2 g of Ti3AlC2 was slowly added to the etching solution in small amounts at a rotation speed of 500 rpm and reacted at 40°C for 48 hours.

3. The method for preparing the photovoltaic nano antibacterial material MXene@MOF according to claim 1, in, In the MOF synthesis step, 3.6 mg, 0.015 mmol Cu(NO 3 ) 2 , 10 μL 1.0 M trifluoroacetic acid, 10.0 mg PVP and 4.0 mg, 0.005 mmol TCPP were hydrothermally synthesized in a 16 mL, V:V=3:1 mixed solution of DMF and ethanol at 80°C for 3 hours.

4. The method for preparing the photovoltaic nano antibacterial material MXene@MOF according to claim 1, in, In the synthesis step of MXene@MOF, 1 mg MXene was dissolved in 16 mL, V:V=3:1 DMF and ethanol, and 4 mg TCPP was added as solution A; 3.6 mg, 0.015 mmol Cu(NO3)2, 10 μL 1.0 M trifluoroacetic acid, and 10.0 mg PVP were dissolved in 48 mL, V:V=3:1 DMF and ethanol as solution B; solution A was slowly added to solution B, and the mixture was reacted at 85°C in a reactor for 3 hours.

5. A photovoltaic nano antibacterial material MXene@MOF, It is characterized in that It is prepared by the preparation method of any one of claims 1 to 4, and has a MXene substrate and a MOF layer, wherein the MOF layer is uniformly coated on the surface of the MXene substrate, so that it integrates dual-path synergistic antibacterial functions of photocatalysis and photothermal function.

6. An antibacterial method using the MXene@MOF material as claimed in claim 5, It is characterized in that The photothermal and photocatalytic capabilities of MXene@MOF materials are stimulated by light to eliminate drug-resistant bacteria.

7. The antibacterial method according to claim 6, in, The MXene@MOF material was irradiated with 808nm near-infrared light.